Edgar Cardoso’s bridge at Quiamafulo, Angola. Design and construction in the late 1950’s of the third viaduct across the River Cuanza - Saldanha, J. L. P. de (Construction History, 2023)
Designed by the leading Portuguese civil engineer Edgar Cardoso, the Quiamafulo Bridge was the third road viaduct to span the Cuanza River in Angola, and the one closest to the country’s capital, Luanda, therefore shortening distances to its sparsely populated hinterland. Located upstream from where the Cambambe dam and hydroelectric facility was being constructed, the Quiamafulo Bridge remained in use until it became submerged in 2017, following the augmentation of that hydroelectric facility, and the resulting enlargement of its reservoir. This called for a fundamental study on this bridge, which eminently served the Angolan road network for more than half a century, focusing on its project and construction. Since bridges take part in larger systems – as river basins do - notes are given on other viaducts built across the Cuanza during the Portuguese colonial period in Angola. Research drew upon previously unpublished sources archived at Lisbon’s Arquivo Histórico Ultramarino (AHU), and from Cardoso’s engineering company; through delving into newspapers published when the dam and bridge were built; comparing this bridge with other structures from that period by Cardoso; and on-site visits.